Employee Performance (Affecting Factor) - Istiqomah; Ainun Ainun; Maulidia Setio Ningsih (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This study aims to determine how the influence of work motivation, and work environment on the performance of employees at Pasir Belengkong District Paser District either partially or simultaneously. The population in this research is all employees of District Office Pasir Belengkong Paser Regency as many as 61 people. The sample is determined by saturated sample technique, with 61 respondents. Data collection methods used were questionnaire (questionnaire) and documentation method. Data analysis method used in this research is descriptive analysis method and multiple linear regression. The results of the hypothesis F test showed F count = 23,461 with the significance value = 0,000 <0.05 This indicates that simultaneously stating That there is influence of motivation and work environment together to employee performance accepted. The result of t test hypothesis is obtained t count from motivation variable equal to 6,806 with significance niali 0.000 <0,05, this explains that there is influence of motivation to employee performance, while work environment variable equal to -, 0495 with significant value equal to 0,623> 0,05 , This explains that there is no effect of work environment on employee performance. Coefficient of determination Adjusted R Square equal to 0,432, this mean 43,2% employee performance at District Office of Pasir Belengkong District Paser Regency influenced by motivation and work environment, while the rest equal to 56,8% influenced by other variable which is outside of variable which researched in research this The conclusion that work motivation significantly influence the performance of employees at Pasir Belengkong District Office Paser District, with a contribution of 44.89%. Working Environment does not significantly affect the performance of Pasir Belengkong District Office employees Paser District, with a contribution of 0.042%. Work motivation and work environment together affect the performance of Pasir Belengkong District Office employees Paser Regency, with 43.2% contribution while the remaining 56.8% influenced by other factors.